Comparisons of sleep apnoea rate and outcomes among patients with resistant and non‐resistant hypertension. Issue 8 (18th July 2016) - Bhandari, Simran K.; Shi, Jiaxiao; Molnar, Miklos Z.; Rasgon, Scott A.; Derose, Stephen F.; Kovesdy, Csaba P.; Calhoun, David A.; Kalantar‐Zadeh, Kamyar; Jacobsen, Steven J.; Sim, John J.
ABSTRACT: Background and objective: We directly compared sleep apnoea (SA) rates and risk of cardiovascular and mortality outcomes among SA patients with resistant hypertension (RH) and non‐RH within a large diverse hypertension population. Methods: A retrospective cohort study between 1 January 2006 and 31 December 2010 among hypertensive adults (age ≥ 18 years) was performed within an integrated health system. Rates of SA in RH and non‐RH were determined. Multivariable logistic regression analyses were used to calculate OR for SA. Cox proportional hazard modelling was used to estimate hazard ratios (HRs) for cardiovascular and mortality outcomes between SA in RH versus SA in non‐RH adjusting for age, gender, race, BMI, chronic kidney disease and other comorbidities. Results: SA was identified in 33 682 (7.2%) from 470 386 hypertensive individuals. SA in RH accounted for 5806 (9.6%) compared to SA in non‐RH 27 876 individuals (6.8%). Multivariable OR (95% CI) for SA was 1.16 (1.12, 1.19), 3.57 (3.47, 3.66) and 2.20 (2.15, 2.25) for RH versus non‐RH, BMI ≥ 30, and males, respectively. Compared to SA in non‐RH individuals, SA in RH had a multivariable adjusted HR (95% CI) of 1.24 (1.13, 1.36), 1.43 (1.28, 1.61), 0.98 (0.85, 1.12) and 1.04 (0.95, 1.14) for ischaemic heart event (IHE), congestive heart failure (CHF), stroke and mortality, respectively. Conclusion: We observed a modest increase in likelihood for SA among RH compared to non‐RH patients. Risks for IHE and CHF were higher for SA in RH compared to SA in non‐RH patients; however, there were no differences in risk for stroke and mortality. Abstract : The risk for ischaemic heart events and congestive heart failure were increased in a large ethnically diverse hypertension (HTN) population with sleep apnoea (SA) and resistant versus non‐resistant HTN. However, there were no differences in risk for stroke and mortality in SA and resistant HTN versus SA and non‐resistant HTN.